1993
DOI: 10.1111/j.1471-4159.1993.tb03501.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Receptor‐Mediated Release of Noradrenaline in the Human Neuroblastoma SH‐SY5Y

Abstract: Dimethylphenylpiperazinium iodide (a nicotinic agonist) evokes noradrenaline release from human neuroblastoma SH-SY5Y cells that have been pretreated with 12-O-tetradecanoylphorbol 13-acetate for 8 min. This effect of dimethylphenylpiperazinium iodide was inhibited by 1 microM mecamylamine but not by 1 microM atropine, which suggests that SH-SY5Y cells express nicotinic receptors coupled to the release of noradrenaline. Dimethylphenylpiperazinium iodide-evoked release was enhanced by 5 microM Bay K 8644 (an L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…However pretreatment of cells with IOOnM TPA for 8 min increases BK-evoked release approximately 2-fold. This suggests that BK-evoked release is enhanced by activation of protein kinase C as has previously been reported in SHSYSY for potassium-and muscarinic receptor M3-evoked [S] and for nicotinic receptorevoked release of NA [3]. The inhibition of BK-evoked release by the B2selective antagonists [D-Phe7]BK and [ThiS,8,DPhe7]BK but not by the BI selective antagonist [Des-Arg9, Leu81BK [ 1 I ] suggests that the 8 2 subtype rather than the BI subtype is coupled to NA release in SHSYSY.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…However pretreatment of cells with IOOnM TPA for 8 min increases BK-evoked release approximately 2-fold. This suggests that BK-evoked release is enhanced by activation of protein kinase C as has previously been reported in SHSYSY for potassium-and muscarinic receptor M3-evoked [S] and for nicotinic receptorevoked release of NA [3]. The inhibition of BK-evoked release by the B2selective antagonists [D-Phe7]BK and [ThiS,8,DPhe7]BK but not by the BI selective antagonist [Des-Arg9, Leu81BK [ 1 I ] suggests that the 8 2 subtype rather than the BI subtype is coupled to NA release in SHSYSY.…”
supporting
confidence: 75%
“…
Our previous studies have shown that cultures of the human neuroblastoma SHSYSY express depolarisation-evoked release of NA stimulated by elevated potassium [ 1.21 or activation of nicotinic receptors [3] which is coupled to L-type calcium channels. In
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While L-, P- and N-type VGCCs have been reported to exist in human neuroblastoma cell lines [65,66,67], the presence of Q-type VGCCs in neurons is unclear. In this study, blockade of the L- and P-type VGCC in either pulse did not prevent E-BSA from activating later genomic transcriptional events from a consensus ERE, suggesting that the role of L- and P-type VGCC is not significant in E-BSA-induced transcription potentiation in SK-N-BE(2)C cells.…”
Section: Discussionmentioning
confidence: 99%